The body of the poet, the body of the nation: corporeality in recent revolution poetry from Belarus. Issue 2 (3rd July 2022) - Achilli, Alessandro
ABSTRACT: This article analyzes representations of the body in Belarusian poetry linked to the 2020 protests. The author argues that the remarkable poetic productivity regarding corporeality, comparable to literary texts inspired by other upheavals, such as the French, Russian, and the most recent Ukrainian revolutions, is directed towards the depiction of a new Belarusian identity shaped by the 2020 revolt against Aliaksandr Lukashenka's latest electoral fraud. On the basis of poetic texts by Iulia Tsimafeeva, Tatstsiana Svetashova, Al′herd Bakharevich, Artur Kamaroŭski, Dmitrii Strotsev, Dmitrii Rubin, and Krystsina Banduryna, the author proposes a reading of the different ways in which living Belarusian poets have represented Belarus, its rethinking of its own identity, and its political struggle through images pertaining to corporeality, including decay, the juxtaposition of masculinity and femininity, violence, and pregnancy. He also argues that in contemporary Belarusian poetry the thematization of the body is related to an important, ongoing, metaliterary reflection on the limits and possibilities of poetry writing in times of change, in the context of revitalized poetry dissemination in the digital age.